MAS1 Receptor Trafficking Involves ERK1/2 Activation through a β-arrestin2-dependent Pathway - Cerniello, Flavia M. (Hypertension, 2017)
The MAS1 receptor (R) exerts protective effects in the brain, heart, vessels and kidney. R trafficking plays a critical function in signal termination and propagation and in R resensitization. We examined MAS1R internalization and trafficking upon agonist stimulation and the role of β-arrestin2 in the activation of extracellular signal-regulated kinase 1/2 (ERK1/2) and Akt following MAS1R stimulation. Human embryonic kidney 293T cells were transfected with the coding sequence for MAS1R-YFP. MAS1R internalization was evaluated by measuring the MAS1R present in the plasma membrane after agonist stimulation using a ligand-binding assay. MAS1R trafficking was evaluated by its colocalization with trafficking markers. MAS1R internalization was blocked in the presence of shRNAcaveolin-1 and with dominant negatives for Eps15 (a protein involved in endocytosed Rs by clathrin-coated pits (CCP)) and for dynamin. After stimulation, MAS1R colocalized with Rab11, a slow recycling vesicle marker, and not with Rab4, a fast recycling vesicle marker, or LysoTracker, a lysosome marker. Cells transfected with MAS1R showed an increase in Akt and ERK1/2 activation upon Ang-(1-7) stimulation, which was blocked when the CCP pathway was blocked. Suppression of β-arrestin2 by shRNA reduced the Ang-(1-7)-induced ERK1/2 activation, while Akt activation was not modified. We conclude that upon agonist stimulation, MAS1R is internalized through CCP and caveolae in a dynamin-dependent manner and is then slowly recycled back to the plasma membrane. MAS1R induced Akt and ERK1/2 activation from early endosomes, and the activation of ERK1/2 was mediated by β-arrestin2. Thus, MAS1R activity and density may be tightly controlled by the cell.